"Date someone your own size": Prejudice and discrimination toward mixed-weight relationships. (June 2017) - Collisson, Brian; Howell, Jennifer L.; Rusbasan, David; Rosenfeld, Emily
We assessed whether people express more prejudice and discrimination toward mixed-weight couples (i.e., romantic partners with dissimilar body mass indexes [BMIs]) than matched-weight couples. In Study 1, people rated mixed-weight couples less favorably than matched-weight couples. In Study 2, people acted as matchmakers; they chose to pair potential relationship partners on the basis of similar BMI and body size. Mixed-weight couples were perceived as poorer matches than matched-weight couples. In Study 3, people offered advice to a person dating a mixed-weight or matched-weight partner. Men and women dating a mixed-weight, rather than matched-weight, partner were advised to go on less active, public, and expensive dates, display less physical affection, and delay introductions to close others. In Study 4, perceived relational inequity, prejudice toward mixed-status relationships, in general, and system justification motives moderated mixed-weight prejudice. Implications for couples are discussed.